Bio-oil production from hydrothermal liquefaction of Pteris vittata L.: Effects of operating temperatures and energy recovery. (October 2018) - Chen, Jinbo
Highlights: Characterization of various products via HTL of Pteris vittata L. The HHV of bio-oil were 19.93–35.45 MJ/kg with a H/C ratio of 1.26–1.46. New insights in HTL of hyper-accumulator biomass for energy reutilization. Abstract: Hyper-accumulator biomass, Pteris vittata L., was hydrothermally converted into bio-oils via hydrothermal liquefaction (HTL) in sub-supercritical water. The distributions and characterizations of various products as well as energy recovery under different temperatures (250–390 °C) were investigated. The highest bio-oil yield of 16.88% was obtained at 350 °C with the hydrothermal conversion of 61.79%, where the bio-oil was dominated by alcohols, esters, phenols, ketones and acidic compounds. The higher heating values of bio-oil were in the range of 19.93–35.45 MJ/kg with a H/C ratio of 1.26–1.46, illustrating its high energy density and potential for use as an ideal liquid fuel. The main gaseous products were CO2, H2, CO, and CH4 with the H2 yield peaking at 22.94%. The total energy recovery from bio-oils and solid residues fell within the range of 37.72–45.10%, highlighting the potential of HTL to convert hyper-accumulator biomass into valuable fuels with high conversion efficiency.